2016
DOI: 10.3168/jds.2015-10077
|View full text |Cite
|
Sign up to set email alerts
|

A method for single nucleotide polymorphism selection for parentage assessment in goats

Abstract: Accurate pedigrees are essential to optimize genetic improvement and conservation of animal genetic resources. In goats, the use of mating groups and kidding management procedures hamper the identification of parentage. Small panels of single nucleotide polymorphisms (SNP) have been proposed in other species to substitute microsatellites for parentage assessment. Using data from the current GoatSNP50 chip, we developed a new 3-step procedure to identify a low-density SNP panel for highly accurate parentage ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…The first goat genome of a Yunnan black female goat was completely assembled and officially released about one year before in 2013 (Du et al 2012;Tosser-Klopp et al 2012;Dong et al 2013). Since the Caprine 52 K SNP chip was recently developed, only a limited number of studies have been reported but they encompass a wide variety of aspects including (i) linkage disequilibrium, population distribution, and structure analyses in several goat breeds (Kijas et al 2013;Nicoloso et al 2015;Lashmar et al 2015); (ii) implementation and development of marker-assisted breeding scheme strategies (Brito et al 2015;Lashmar et al 2015); (iii) development of SNP chipbased caprine parentage tests (Talenti et al 2016); and (iv) signatures of selection and GWAS analyses for phenotypic traits and adaptation (Becker et al 2015;Kim et al 2015;Reber et al 2015). Italy is a country that can be considered an important reservoir of genetic resources for goat species in Europe.…”
Section: U N C O R R E C T E D P R O O F Introductionmentioning
confidence: 99%
“…The first goat genome of a Yunnan black female goat was completely assembled and officially released about one year before in 2013 (Du et al 2012;Tosser-Klopp et al 2012;Dong et al 2013). Since the Caprine 52 K SNP chip was recently developed, only a limited number of studies have been reported but they encompass a wide variety of aspects including (i) linkage disequilibrium, population distribution, and structure analyses in several goat breeds (Kijas et al 2013;Nicoloso et al 2015;Lashmar et al 2015); (ii) implementation and development of marker-assisted breeding scheme strategies (Brito et al 2015;Lashmar et al 2015); (iii) development of SNP chipbased caprine parentage tests (Talenti et al 2016); and (iv) signatures of selection and GWAS analyses for phenotypic traits and adaptation (Becker et al 2015;Kim et al 2015;Reber et al 2015). Italy is a country that can be considered an important reservoir of genetic resources for goat species in Europe.…”
Section: U N C O R R E C T E D P R O O F Introductionmentioning
confidence: 99%
“…In goats, SNP arrays have been used for parentage testing (Talenti et al . ), to investigate genetic diversity and population structure (Nicoloso et al . ; Visser et al .…”
Section: Discussionmentioning
confidence: 99%
“…To identify individuals with high relatedness (e.g., parent–offspring pairs), we used an in-house script to calculate the number of Mendelian errors (ME) in pairwise comparisons between all individuals [ 37 ]. Pairs of animals with less than 100 ME were considered as related [ 38 ].…”
Section: Methodsmentioning
confidence: 99%